2022
DOI: 10.3389/fcvm.2022.869076
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Left Atrial and Ventricular Strain for the Detection of Atrial Fibrillation in Patients With Cryptogenic Stroke

Abstract: Background and AimsCryptogenic stroke (CS) is associated with a high rate of recurrences and adverse outcomes at long-term follow-up, especially due to its unknown etiology that often leads to ineffective secondary prevention. Asymptomatic atrial fibrillation (AF) could play an important pathophysiological role. Some studies have pointed to left atrial (LA) and left ventricular (LV) systolic and diastolic dysfunction as surrogate markers of AF. The aim of the study is to evaluate the relationship between echoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…It was reported by two independent groups of researchers (37,38) Notably, it was concluded in 2020 (39) that patient who developed AF had significantly larger LA volumes and lower LAEF than participants free of AF which…”
Section: Discussionmentioning
confidence: 99%
“…It was reported by two independent groups of researchers (37,38) Notably, it was concluded in 2020 (39) that patient who developed AF had significantly larger LA volumes and lower LAEF than participants free of AF which…”
Section: Discussionmentioning
confidence: 99%
“…We therefore examined meta‐regression bubble plots and performed an exclusion analysis to identify outlier studies for sources of influence. A number of studies were identified over all meta‐analysis studies, with resolution of heterogeneity observed following their exclusion 6,16,21–23,26,28,30,32,34,35,37,39 . Notably, the majority of outlier studies were observed in studies comparing CS‐ESUS to HC, indicating probable unidentified clinical covariates in patients compared with healthy participants.…”
Section: Discussionmentioning
confidence: 99%
“…visible outlier studies, and also performed a rigorous exclusion protocol by sequentially leaving out one or more studies from each analysis, in order to identify influential studies for potential sources of variation (Table 4). 6,16,[21][22][23]26,28,30,32,34,35,37,39 Following outlier omission, variability was significantly reduced for all LA metrics, after controlling for age (I 2 < 40% for all variables). Due to the number of outlier studies, potential for pooled effect bias/distortion, reduction in generalizability following exclusion and lack of single obvious cause of outlier status, 13 we maintained these studies within the analysis and performed a thorough exploration for sources of discrepancy.…”
Section: Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, peak atrial contraction strain (PACS) was an independent predictor of AF occurrence in patients with cryptogenic stroke. 10 Peak atrial longitudinal strain (PALS) and PACS were correlated with POAF in patients undergoing surgical treatment of aortic stenosis. 11 Recent studies suggested a potential association between impaired LA strain at baseline and POAF in patients undergoing CABG.…”
mentioning
confidence: 99%